Bio-inspired anti-impact manipulator for capturing non-cooperative spacecraft: theory and experiment. (August 2020) - Dai, Honghua; Cao, Xuyang; Jing, Xingjian; Wang, Xin; Yue, Xiaokui
Highlights: A novel bio-inspired anti-impact manipulator (BAM) was proposed to suppress the vibration of the servicing spacecraft subject to an impulsive force. The BAM system is superior to the traditional system in terms of both decay time and vibration strength. An interesting stick-slip phenomenon is discovered in the present system. A corresponding ground experiment is carried out to verify the validation of the theoretical modeling and numerical simulations of the BAM system. Abstract: On-orbit capture of non-cooperative targets, i.e., malfunctioning satellites and space debris, is nowadays an urgent task. It is also a challenging task since the states of the non-cooperative targets are essentially unknown and have to be estimated by real-time visual detection. In the final approach stage, inevitable time-delay and measurement errors of the visual detection may cause a sudden impact between the servicing spacecraft and target, which can make the spacecraft unstable or even tumbling. Therefore, the compliant capture of a non-cooperative target is the key issue for the modern on-orbit servicing missions. The 'robotic arm plus gripper' type manipulator is normally used to capture space targets. However, sudden impact induced from the target cannot be efficiently suppressed in this conventional manipulator. To solve this limitation, inspired by animal limb structures, a novel bio-inspired anti-impact manipulator (BAM), consisting of a capture element, a bio-inspired structure and a buffer element, is proposed for the first time. The dynamical responses and isolation performance of the presently proposed BAM system are studied both theoretically and experimentally. In theoretical analysis, the mathematical model of the BAM system, described by a set of non-smooth ordinary differential equations, is established by the Lagrangian mechanics. The effects of system parameters are thoroughly investigated to verify the performance of the anti-impact system in various working conditions. In addition, the corresponding ground experiment is carried out to compare with the theoretical analysis. An interesting stick-slip phenomenon induced by the free-play nonlinear friction is observed in both theoretical and experimental studies. Finally, it is shown that the experimental result agrees well with the theoretical one, which verifies efficiency of the present BAM system.